How does livelihood capital influence the green production behaviors among professional grain farmers cultivating high-quality rice? - Zhang, Bin; Mao, Wenyi; Hu, Zhen; Cai, Yingshu; Xie, Ning; Weng, Zhenlin (Frontiers in Nutrition, 2025)
IntroductionAs a vital food crop in China, the sustainable production of high-quality rice is essential for ensuring food security and facilitating the green transformation of agriculture. However, the limited adoption of green production technologies for high-quality rice among farmers poses a significant obstacle to the sustainable development of the grain sector. While previous studies have primarily focused on the adoption of green technologies by traditional farmers, there has been a lack of attention on professional grain farmers as a distinct category of agricultural operators.MethodsThis study, based on the sustainable livelihood framework, focuses on professional grain farmers. By analyzing data from 655 professional grain farmers in Jiangxi Province and utilizing the ordered logit model, we analyzed and validated the influence of livelihood capital on the green production behaviors. Additionally, we applied mediating and moderating effect models to clarify the roles of value cognition and government regulation in this relationship.ResultsThe study found the following: (1) livelihood capital significantly and positively affects the green production behaviors of professional grain farmers. Specifically, human capital, natural capital, financial capital, and social capital all contribute to the adoption of green production practices. (2) The relationships between livelihood capital and green production behavior are partially mediated by perceptions of economic, ecological, and social benefits, with the mediating effects ranked in descending order. (3) Government regulation acts as a moderator, where stronger incentive and guidance policies amplify the influence of livelihood capital on professional grain farmers’ green production behaviors. (4) Heterogeneity analysis indicates that livelihood capital and value perception have a more pronounced effect on green production behaviors among farmers with higher levels of livelihood capital.DiscussionBased on these results, the study suggests enhancing the allocation of farmers’ livelihood capital, intensifying the dissemination and education of green production technologies, and strengthening policy incentives and guidance.